In vitro antiviral activity of peptide‑rich extracts from seven Nigerian plants against three non‑polio enterovirus species C serotypes (2021)
Background: As frequent viral outbreaks continue to pose threat to public health, the unavailability of antiviral drugs and challenges associated with vaccine development underscore the need for antiviral drugs discovery in emergent moments (endemic or pandemic). Plants in response to microbial and pest attacks are able to produce defence molecules such as antimicrobial peptides as components of their innate immunity, which can be explored for viral therapeutics. Methods: In this study, partially purified peptide-rich fraction (P-PPf ) were obtained from aqueous extracts of seven plants by reverse-phase solid-phase extraction and cysteine-rich peptides detected by a modified TLC method. The peptide-enriched fractions and the aqueous (crude polar) were screened for antiviral effect against three non-polio enterovirus species C members using cytopathic effect reduction assay. Results: In this study, peptide fraction obtained from Euphorbia hirta leaf showed most potent antiviral effect against Coxsackievirus A13, Coxsackievirus A20, and Enterovirus C99 (EV-C99) with IC50< 2.0 μg/mL and selective index ≥ 81. EV-C99 was susceptible to all partially purified peptide fractions except Allamanda blanchetii leaf. Conclusion: These findings establish the antiviral potentials of plants antimicrobial peptides and provides evidence for the anti-infective use of E. hirta in ethnomedicine. This study provides basis for further scientific investigation geared towards the isolation, characterization and mechanistic pharmacological study of the detected cysteine-richpeptides.